The Biological Importance of Polynyas in the Canadian Arctic - Stirling, Ian (ARCTIC, 1980)
Polynyas are areas of open water surrounded by ice. In the Canadian Arctic, the largest and best-known polynya is the North Water. There are also several similar, but smaller, recurring polynyas and shore lead systems. Polynyas appear to be of critical importance to arctic marine birds and mammals for feeding, reproduction and migration. Despite their obvious biological importance, most polynya areas are threatened by extensive disturbance and possible pollution as a result of proposed offshore petrochemical exploration and year-round shipping with ice-breaking capability. However, we cannot evaluate what the effects of such disruptions might be because to date we have conducted insufficient research to enable us to have a quantitative understanding of the critical ecological processes and balances that may be unique to polynya areas. It is essential that we rectify the situation because the survival of viable populations or subpopulations of several species of arctic marine birds and mammals may depend on polynyas.